Effects of neem, betel leaf, devil's tree, jute and turmeric against gastrointestinal nematodes in sheep (Journal of the Bangladesh Agricultural University, 2011)
Effects of neem, betel leaf, devil’s tree, jute and turmeric against natural gastrointestinal nematodes in sheep and on some hematological parameters (TEC, Hb and PCV) and body weight were studied. Thirty (30) naturally parasitized sheep were randomly divided into six groups(A, B, C, D, E and F), each consisting of five sheep. Ten percent water extract of leaves of neem, betel leaf, devil’s tree and jute were administered orally to the sheep of group A, B, C and D, respectively. Sheep of group E was treated orally with 10% water extract of rhizome of turmeric. Sheep of group F was kept as infected control group. Fecal samples, hematological parameters and body weight were examined before treatment and on 7th, 14th, 21st and 28th day. A significant (p